THE RELATIONSHIP OF AGE AND OCCUPATION ON THE INCIDENCE OF KERATITIS AND CORNEAL ULCERS IN PATIENTS VISITING AT HOSPITAL DR.H.ABDOEL MOELOEK LAMPUNG PROVINCE IN 2013-2014 - Rahmat Syuhada; Rakhmi Rafie (Jurnal Ilmu Kedokteran dan Kesehatan, 2019)
Keratitis is an inflammation of one of the five layers of the corneadue to the infiltration of inflammatory cells in the cornea which will result in the corneato become cloudy. many factors that influence the occurrence of keratitis, one of thefactors of age and occupation. Keratitis may affect all ages but more frequently inadulthood because that is of productive age, so at that age more at risk of trauma. One ofthe complications arising from keratitis is corneal ulcers.Objective: Determining the relationship of age and occupation on the incidenceof keratitis and corneal ulcers in patients at hospitals Dr.H.Abdoel Moeloek LampungProvince in 2013-2014.Methods: Thisstudyis aretrospectiveanalytical researchwith cross sectionalapproach. Thestudypopulationwasallpatients withkeratitisandcorneal ulcersinhospitalsDr.H.AbdoelMoeloekLampung Provincein2013-2014.sampleswereobtainedbased on the formulaSlovinandinclusion and exclusion criteriainthisstudy amounted to64 keratitis patientsand97 corneal ulcers patientswith a totalof161patientsandtaken usingPurposive Sampling.Results:Theresearch usingChi-square testshowed thatthe relationship ofagetooccupationin patients withkeratitis(p =0.009) withOddsRatio=5.000andtherelationship of agetoemploymentin patients withcorneal ulcers(p =0.021)withOddsRatio=3.250.Conclusion:The results of this study can be concluded that there is a relationshipbetween age and occupation on the incidence of keratitis and corneal ulcers in patientsvisiting at hospitals Dr.H.Abdoel Moeloek Lampung Province in 2013-2014 and the ageand occupation is a risk factor for keratitis and corneal ulcers.